Influence of machining parameters on fatigue endurance limit of AISI 4140 steel - Lopes,Karina S. S. (2008)
The general purpose of this research is to study the influence of commercial machining parameters on fatigue limits of steels. Specifically in this work, the influence of cutting speeds, depth of cut, feed rate and residual stresses of turned surfaces of AISI 4140 steel specimens on fatigue strength were analyzed. In some specimens, the residual stress was eliminated by heat treatment. The fatigue experiments were carried out at room temperature, applying a cyclical frequency of 58Hz, with mean stress equal to zero (R=-1), on a rotating-bending fatigue testing machine of the constant bending moment type. It was used the staircase (or up-and-down) method to determine the fatigue limit of the specimens.